2005
DOI: 10.1007/s10646-004-1353-6
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides and Arable Weeds: Effects on Germination and Seedling Growth

Abstract: The decline of many arable weed species in Northern Europe has been attributed to the intensification of modern agriculture and in particular, increasing pesticide use. In this study, we examined the effect of two insecticides, dimethoate and deltamethrin, on the germination and seedling growth of six arable weed species. Although germination was unaffected by insecticide application, seedling growth of four species was decreased by exposure to deltamethrin (Capsella bursa-pastoris and Poa annua), dimethoate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…Kobayashi (2004) suggested that it is due to the physiological and biochemical characteristics of each species. The different responses to the same allelopathic extract can also be due to the seed structure (Hodgson & Mackey 1986) and seed coat penetrability (Hanley & Whiting 2005). Haq et al (2010) suggested that a mixture of a variety of compounds in the extract may act in an antagonistic or synergistic ways in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi (2004) suggested that it is due to the physiological and biochemical characteristics of each species. The different responses to the same allelopathic extract can also be due to the seed structure (Hodgson & Mackey 1986) and seed coat penetrability (Hanley & Whiting 2005). Haq et al (2010) suggested that a mixture of a variety of compounds in the extract may act in an antagonistic or synergistic ways in different plant species.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2). Th e infl uence of the extracts on germination depends on the size and permeability of the seed coat (Hanley & Whiting 2005). Th e species-dependent response to the allelochemicals shows that they are fundamental not only in natural environments, where they infl uence fl oristic composition, but also in agriculture, where they can be used as selective herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…1). The different germination reaction may be related to seed size and seed structure (Hodgson and Mackey 1986) as well as differences in seed coat penetrability (Hanley and Whiting 2005). In addition to germination, both weed species also differed in their growth response to P. harmala aqueous extracts.…”
Section: Discussionmentioning
confidence: 99%